2018
DOI: 10.1371/journal.pone.0194931
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nationwide supplementary immunization in Lao People's Democratic Republic: Population-based seroprevalence survey of anti-measles and anti-rubella IgG in children and adults, mathematical modelling and a stability testing of the vaccine

Abstract: BackgroundMeasles outbreaks have occurred in some countries despite supplementary immunization activities (SIA) using measles-containing vaccine with high vaccination coverage. We conducted a cross-sectional seroprevalence survey to estimate population immunity in Lao People's Democratic Republic where repeated mass immunization has failed to eliminate measles.Methods and findingsIn this nationwide multistage cluster sampling survey conducted in 2014 based on probability proportionate to size sampling, blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 23 publications
3
45
0
Order By: Relevance
“…The present study also failed to evaluate regional variations in complete vaccination coverage, as the small number of children in each state/region would have produced a low statistical power. Moreover, other countries have had discrepancies between the vaccination coverage rate and population-level immunity for vaccine-preventable diseases, which may be related to insufficient cold chain control and the vaccine’s heat sensitivity [39]. Thus, to evaluate the risks of related outbreaks, direct immunity assessment is needed (e.g., seroepidemiological analysis).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also failed to evaluate regional variations in complete vaccination coverage, as the small number of children in each state/region would have produced a low statistical power. Moreover, other countries have had discrepancies between the vaccination coverage rate and population-level immunity for vaccine-preventable diseases, which may be related to insufficient cold chain control and the vaccine’s heat sensitivity [39]. Thus, to evaluate the risks of related outbreaks, direct immunity assessment is needed (e.g., seroepidemiological analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Despite levels of coverage reported for measles vaccination of above the herd immunity threshold (the coverage required to control transmission 3 ), measles outbreaks continue to occur in some countries. In Lao PDR, for example, supplemental immunization campaigns (SIAs) of measles and the measles-rubella vaccine reported coverage of 96% in 2007 and 97% in 2011 respectively, targeting wide age ranges (children aged 9 months-14 years and 9 months – 19 years respectively), and outbreaks were reported in 2012, 2013 and 2014 4 . The factors contributing to these ongoing outbreaks are poorly understood, but need to be elucidated if targets specified in the Global Vaccine Action Plan of measles elimination in 5 world regions by 2020 5 are to be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Vietnam found marked discrepancies between estimated levels of population protection and vaccine coverages of measles [5]. Reported immunization coverage does not necessarily offer reliable information with which to estimate population immunity [12,21,22].…”
Section: Mumpsmentioning
confidence: 94%
“…As the sampling design of the present study was derived from other purposes, comparison with results from different times (past and future) and different places (regions in Vietnam and other countries) is di cult. To reveal the current population immunity and to contribute to the formulation of immunization policy, more samples (i.e., ≥2,000 samples) from wider geographical areas are needed [12,21].…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation